1970
DOI: 10.1159/000270883
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Processes in Discrimination Learning

Abstract: A review of the discrimination-learning behavior of children indicates that two general theoretical orientations have been mainly responsible for guiding recent research, the mediational-attention conception, and a coordinated single-unit and mediational S-R formulation. Results from discrimination-shift studies are analyzed in terms of these two models and the influence on discrimination learning of verbal labels and other forms of symbolic representational responses are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0

Year Published

1972
1972
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…A dual basis for discrimination learning in children has been suggested before. These findings are strongly reminiscent of the extensive body of research comparing reversal and extra-dimensional shift performances (Kendler & Kendler, 1970;Lowenkron, 1969;Wolff, 1967). Those data, acquired from a developmental viewpoint, showed that children about the age of the present subjects generally tend to learn simple discriminations, involving multidimensional stimuli, in an unmediated singleunit fashion.…”
Section: Discussionsupporting
confidence: 64%
“…A dual basis for discrimination learning in children has been suggested before. These findings are strongly reminiscent of the extensive body of research comparing reversal and extra-dimensional shift performances (Kendler & Kendler, 1970;Lowenkron, 1969;Wolff, 1967). Those data, acquired from a developmental viewpoint, showed that children about the age of the present subjects generally tend to learn simple discriminations, involving multidimensional stimuli, in an unmediated singleunit fashion.…”
Section: Discussionsupporting
confidence: 64%
“…6-1). Formal theories of discrimination learning are concerned with the details of several effects that Sutherland (1964) related to his two-stage model: the transfer of discrimination training along a dimension (Sutherland, Mackintosh & Mackintosh, 1965); the reversal shift effect (Kendler & Kendler, 1962; and the overtraining reversal effect (Lovejoy, 1966(Lovejoy, , 1968Mackintosh, 1964Mackintosh, , 1965Wolford & Bower, 1969).…”
mentioning
confidence: 99%
“…In a previous study which used college students as subjects (Labouvie, Frohring, Baltes, & Goulet, 1973), an attempt was made to specify those processes by proposing that interactions between ability measures and learning tasks reflect the use of common strategies or skills. Based on the associative-conceptual distinction inherent in many current formulations of developmental learning processes (Goulet, 3973;Jensen, 1971;Kendler & Kendler, 1970), it was expected that the pattern of intercorrelations between ability variables and learning effectiveness would reflect the extent to which subjects used (or did not use) a conceptual strategy. The task selected was free-recall learning, and an attempt was made to manipulate the degree to which subjects would rely on a conceptual strategy, namely subjective organization (Tulving, 1968).…”
mentioning
confidence: 99%